Iz zgodovine slovenske poetike. Rokopisni osnutek prozodije Blaža Kumerdeja - Scherber, Peter (Jezik in slovstvo, 2021)
The Slovenian educator and Enlightenment figure Blaž Kumerdej wrote a handwritten fragment in 1791 as the second part of his attempt at a Carniolan-Slavonic grammar. Written in German, this document consists of a preface that is a genuine “defence” of the Slavic/Slovenian language, while the main part is a fragment of a treatise on “Carniolan-Slovenian” prosody, as well as on rhymes and figures. This draft is as yet untranslated and unpublished. The present article provides a survey of the research done so far as well as a brief overview of the document. The focus is on the intentions of the Enlightenment scholar Kumerdej as discussed in the preface, in which he presents his arguments with the aid of the well-known example of the “noble savage”. The document can be interpreted as an example of the Enlightenment tradition of the “defence of language”.
Keywords: Enlightenment; Kumerdej, Blaž; manuscript; poetics; poetika; prosody; prozodija; razsvetljenstvo; rokopis